From Integration to Contact - Paul Larsson (Nordisk Politiforskning)
Abstract This article deals with the reform named nærpolitireformen, literarlly translated “the near police reform” in Norway. There is a wide gap between the political retorics talking about community policing and the reality, that is bigger centralized units. The article analyses the solutions suggested to make the police local; the police contacts, police Councils and the SLT. It asks does these measures make the police local and what sort of police will we get after the reform?